(untitled) (Historia Agraria de América Latina, 2024)
The article analyzes concerns regarding fires and speculations about a probable process of desertification in the region of Central Brazil, in the first decades of the 20th century, based on the short story “Gente da Gleba”, by Goiás writer Hugo de Carvalho Ramos (1895 -1921). This analysis is carried out by comparing the perceptions of Ramos, local inhabitants, scientists, and travelers at the time about a possible change in the rainfall regime in Central Brazil at the beginning of the 20th century, caused by fires in the dry season and consequent destruction of the forests. This is a study possible through an approach that brings together Environmental History and Ecocriticism when investigating how non-humans impact a literary work in a given historical period. The concerns outlined in the work “Gente da Gleba” are related to different perspectives on the Cerrado biome and the management of fire in this area, at the beginning of the 20th century, but also with desiccation theories, which were a set of scientific ideas that forged a direct association between deforestation and climate change at the local level.